INVESTIGATING PEDAGOGICAL PRACTICE AS A KEY ELEMENT IN TEACHER EDUCATORS’ WORK AT THE FEDERAL INSTITUTES: FROM EXISTING ACTIONS TO DESIRED ACTIONS - Paniago, Rosenilde Nogueira (2021)
This paper draws from a post-doctoral research project aimed at discussing the contribution of research on pedagogical practice as a possibility to improve teaching and learning and to fostering the professional development of teacher educators. It also aims to analyse the current conditions for professional development opportunities in light of other contexts, namely experiences at the University of Minho, Portugal, and at the University of Applied Sciences, Finland. This paper focuses on the possibilities and challenges related to researching pedagogical practice of teacher educators taking into account the experience of Portugal and Finland in order to discuss not only existing actions and also desired actions. A narrative-biographical approach is used with five Brasilian teacher educators, one from Portugal and one from Finland. The multiciplicity of actions on the tripod, research, extension in the vertical teaching from high school to postgraduate, added to the lack of training, weakens the materiality of pedagogical research. The implementation of study groups can alleviate the challenges.